Diseases of the chest, heart and vascular system 2025-2028. - Hodler, Jürg; Kubik-Huch, R. A.; Roos, Justus E.
This open access book offers an essential overview of chest, heart and vascular system imaging. Over the last few years, there have been considerable advances in this area, driven by both clinical and technological developments. Written by leading international experts and teachers, the chapters are disease-oriented and cover all relevant imaging modalities, with a focus on magnetic resonance imaging and computed tomography. IDKD books are rewritten (not merely updated) every four years, which means they offer a comprehensive review of the state-of-the-art in imaging. The book is clearly structured and features learning objectives, abstracts, subheadings, tables and take-home points, supported by design elements to help readers navigate the text. It will particularly appeal to general radiologists, radiology residents, and interventional radiologists who want to update their diagnostic expertise, as well as clinicians from other specialties who are interested in imaging for their patient care.
Keywords: Heart -- Imaging.; Chest -- Diseases -- Imaging.; Lungs -- Diseases -- Imaging.; Chest -- Diseases.; Lungs -- Diseases.; Thoracic Diseases; Lung Diseases; Cœur -- Imagerie.; Thorax -- Maladies.; Poumons -- Maladies.; Electronic books.